Kentucky's governors - Harrison, Lowell H. (Lowell Hayes), 1922-2011 (University Press of Kentucky, 2004)
These essays profile every chief executive of the Bluegrass State from eighteenth-century governor Isaac Shelby to Ernie Fletcher. First published in 1985, this edition of is expanded and revised to include governors Wilkinson, Jones, Patton, and Fletcher, as well as new information on respected figures such as Louie B. Nunn. An introduction by one of Kentucky's historian laureates, Thomas D. Clark, provides key insights into successive governors' evolving constitutional powers.